The Role of Mobile Based Accounting Information Systems for MSMEs Perfomance - Sinarwati, Ni Kadek; Sujana, Edy; Herawati, Nyoman Trisna (International Journal of Psychosocial Rehabilitation, 2020)
The implementation of a mobile-based Accounting Information System (AIS) that can help compile financial statements is highly awaited by MSMEs. The results of the first research in the form of mobile- based AIS prototypes have been piloted to several MSMEs, the trial results provide information that MSMEs are very much waiting for the presence of Appropriate Technology in the form of an AIS application that will be used in assisting the administration of their business. This research applies appropriate technology in the form of mobile- based accounting information system applications/software for MSMEs. The specific objective to be achieved is to test the effectiveness of the system in improving the performance of MSMEs. This study aims to evaluate the effectiveness of mobile-based AIS for MSMEs. A type of summative evaluation research that emphasizes product capabilities in this case appropriate technology in the form of AIS applications. Evaluation actions are carried out by measuring the performance of MSMEs before and after using AIS in managing their business. AIS is declared effective if there are significant differences in MSMEs performance. Data analysis techniques used in evaluating system effectiveness are qualitative descriptive analysis.The results showed that there were differences in the business performance of MSMEs with indicators after the implementation of AIS of MSME business administration was more neat and organized than before the implementation of AIS.